2017
DOI: 10.1136/jclinpath-2016-204231
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics associated with requests by pathologists for second opinions on breast biopsies

Abstract: Aims Second opinions in pathology improve patient safety by reducing diagnostic errors, leading to more appropriate clinical treatment decisions. Little objective data are available regarding the factors triggering a request for second opinion despite second opinion consultations being part of the diagnostic system of pathology. Therefore we sought to assess breast biopsy cases and interpreting pathologists characteristics associated with second opinion requests. Methods Collected pathologist surveys and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(17 reference statements)
0
2
0
1
Order By: Relevance
“…Since only eight identified patients declined study participation, we estimate this potential bias as minimal. Although high MD it is not stated as an obstacle in guidelines concerning pathological evaluation after NACT for BC [51], a few studies indicate that pathological evaluation is more difficult in a high MD specimen [52, 53]. We expect this potential bias to be negligible in our results.…”
Section: Discussionmentioning
confidence: 74%
“…Since only eight identified patients declined study participation, we estimate this potential bias as minimal. Although high MD it is not stated as an obstacle in guidelines concerning pathological evaluation after NACT for BC [51], a few studies indicate that pathological evaluation is more difficult in a high MD specimen [52, 53]. We expect this potential bias to be negligible in our results.…”
Section: Discussionmentioning
confidence: 74%
“…Allison et al in their analysis of the meetings of an expert review panel broadly identified root causes of disagreement as being related to the pathologist, diagnostic coding, methodology, or specimen 19 . Furthermore, Geller et al found increased requests for second opinions were associated with atypia (ADH or ADH in a papilloma), increased mammographic breast density seen radiologically prior to biopsy, or where many co‐existing histological diagnoses were present 20 …”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Um estudo americano com 115 patologistas incumbidos de analisar biopsias mamarias mostrou que os mesmos solicitaram segunda opinião em 70% dos seus laudos. 12 A mesma postura foi vista com lesões suspeitas para melanoma num relato da sociedade americana de dermatologia; os patologistas solicitaram voluntariamente a segunda opinião para a formulação de diagnósticos em 85% dos casos. Alguns centros de patologia já possuem políticas internas que direcionam o patologista para uma segunda opinião obrigatória dependendo do conteúdo do laudo.…”
unclassified